Epistemological Foundations of Multidisciplinary Islamic Religious Education: A Reading of Muhammad Abid al-Jabiri at the University Level - Ulil Hidayah; Abdul Haris; Abdul Haris; Imro Atus Soliha; Benny Prasetiya (International Journal of Educational Narratives, 2026)
Background. The increasing demand for knowledge integration in Islamic higher education has intensified discussions on the epistemological foundations of Multidisciplinary Islamic Religious Education (IRE). However, existing studies on Muhammad Abid al-Jabiri’s epistemological framework largely focus on its philosophical dimensions, with limited attention to its potential contribution to the reconstruction of contemporary Islamic educational paradigms. Purpose. This study aims to analyze the relevance of al-Jabiri’s epistemology and explore its contribution to the development of Multidisciplinary Islamic Religious Education in Islamic universities. Methods. Employing a qualitative library research design, the study utilized descriptive-analytical interpretation and thematic synthesis to examine primary and secondary sources related to bayani, irfani, and burhani epistemologies. Results. The analysis generated four major themes: (1) bayani epistemology as the normative foundation of Islamic education, (2) irfani epistemology as the ethical and spiritual dimension of learning, (3) burhani epistemology as the driver of scientific and multidisciplinary development, and (4) an integrative epistemological model for Multidisciplinary Islamic Religious Education. The literature synthesis indicates that the three epistemological traditions function in a complementary rather than competing manner. Bayani provides normative and theological grounding, irfani contributes ethical-spiritual depth, while burhani supports critical inquiry and scientific reasoning. Their interaction forms an integrative framework that bridges revelation, spirituality, and rational inquiry. This model further supports curriculum development, interdisciplinary learning, and research innovation within Islamic higher education institutions. Conclusions. Multidisciplinary Islamic Religious Education can be understood as an epistemological reconstruction effort that integrates religious and scientific knowledge. The study concludes that al-Jabiri’s epistemological framework offers a conceptual foundation for producing graduates who are intellectually competent, spiritually grounded, and socially responsible.